The Influence of Learners’ Age on the Acquisition of Phonology and Syntax in Second Language: a Theoretical Overview - Achmad Farid (Journal of Research in Foreign Language Teaching (JRFLT), 2021)
Whether there is a critical period for second language learning or not remains a mystery. Many researchers have attempted to investigate the effects of age on a second language acquisition, but they come up with different results (c.f. Lenneberg, 1967; e.g. Oyama, 1976; ; Snow & Hoefnagel-Hohle, 1978; O’grady, 1989; Long, 1990; Newport, 1989; Chiswick and Miller, 2008; Rothman, 2008). By reviewing a range of scientific studies in age effect on the acquisition of second language, the authors attempts to reveal whether younger learners acquire language better than their older counterparts and whether critical period in language learning affect all language modules. The studies indicate that, in terms of phonology, the younger the learners exposed to a second language the more likely they achieve native accent. In contrast, learners who are exposed to a second language at a later age would most likely speak a foreign accent. For the acquisition of syntax, the same circumstance applies.